METHODOLOGIES FOR STERILIZATION OF RENAL SCAFFOLDS: A MINI-LITERATURE REVIEW (CIPEEX, 2026)
Introduction: Tissue bioengineering is advancing in the creation of viable scaffolds for applications with various cell types. However, one of the biggest challenges for the clinical use of these biomaterials is the sterilization step. After the decellularization process, the resulting scaffold must be completely sterile. The method used must eliminate all microbial contaminants without compromising the delicate structure and biological components of the matrix, which would render its therapeutic application unfeasible. Objective: To evaluate the main sterilization methods for renal scaffolds for clinical use. Methods: Using the PICO strategy, the guiding question was determined, and articles were searched for in the search engines PubMed Central (PubMed), Virtual Health Library (VHL), and Sciello, using the appropriate descriptors according to DECS/MesH. Thirteen articles were selected for this integrative review. Results: Conventional methods such as gamma irradiation and autoclaving, while effective, severely compromise the structural and biological integrity of the scaffold, making them unsuitable. Ethylene oxide (ETO) emerges as a less destructive alternative, but its inherent risk of residual cytotoxicity limits its application. In this context, peracetic acid (PAA), when used under optimized conditions, represents the most balanced approach, ensuring sterility with minimal damage to the matrix and promoting a robust cellular response. Conclusion: The choice of sterilization method directly impacts the viability of ECM scaffolds. However, traditional methodologies are not suitable for highly sensitive biomaterials such as kidney tissue, necessitating new techniques that, while effective, require further testing.